Postural orthostatic tachycardia syndrome is associated with platelet storage pool deficiency. Issue 37 (September 2016) - Gunning, William T.; Karabin, Beverly L.; Blomquist, Thomas M.; Grubb, Blair P.
Abstract : Abstract: Mechanisms have been postulated to explain postural orthostatic tachycardia syndrome (POTS), however, the etiology of this often debilitating disorder remains unknown. We conducted a retrospective case–control study of 181 POTS patients who exhibited/reported bleeding symptoms for a specific platelet (PL) dysfunction disorder, delta granule storage pool deficiency (δ-SPD). Patients were included only if results of blood tests for δ-SPD were available. Electron microscopy was utilized to diagnose δ-SPD. An ELISA assay was used to determine serotonin (5HT) concentration in PLs and medical record review was employed to collect patients' clinical symptoms. The most common bleeding symptom was easy bruising (71%) but frequent nose bleeds, heavy menstrual bleeding, and a family history of bleeding were also commonly reported. Of the patients studied, 81% were diagnosed with δ-SPD. Our investigation of 5HT concentration extracted from PLs revealed significantly lower levels of 5HT in POTS patients when compared to that of control subjects. Our data suggest that patients with POTS have significant comorbidities including bleeding symptoms and/or family bleeding histories, and have diminished PL 5HT levels supporting the hypothesis that POTS is a low 5HT level disorder. While we describe a significant relationship with POTS and δ-SPD, this finding does not constitute an etiology for POTS. Our results establish an additional comorbidity frequently seen in POTS that could explain a number of disparate symptoms often affecting the severity of POTS.